Defect management by a cesium fluoride-modified electron transport layer promotes perovskite solar cells. Issue 37 (14th September 2022) - Xu, Xiangning; Lin, Zhichao; Cai, Qingbin; Dong, Hongye; Wang, Xinli; Mu, Cheng
Abstract : The high efficiency perovskite solar cells (PSCs) were achieved by using CsF to manage the defects in the electron transport layer (ETL) of SnO2 . Abstract : SnO2 is a candidate material for electron transport layers (ETLs) in perovskite solar cells (PSCs). However, a large number of defects at the SnO2 /perovskite interface lead to notable non-radiative interfacial recombination. Moreover, the energy level arrangement between SnO2 /perovskite does not match well. In this study, a SnO2 /CsF-SnO2 double-layer ETL was prepared by doping CsF into SnO2, effectively passivating the defects of the SnO2 ETL and SnO2 /perovskite interface. The formation of a good energy level arrangement with the perovskite layer reduces the interface non-radiative recombination and improves the performance of the interface charge extraction. The photoelectric conversion efficiency of the optimal CsF-modified PSC reached 22.18%, owing to the significant increase in the open-circuit voltage to 1.180 V.